Continuities and Discontinuities of Patronage and Familism in The Way of Doing Politics in Tumaco (Colombia) - Rosero García, Edgar Armando (Sociedad y Economía, 2012)
This article develops a brief description of the electoral political process in the municipality of Tumaco (Nariño), from the comparison of elections for the Mayor and the Municipal Council carried out in the period 1988-2007, which shows the struggle for local political power among the different political force, having impact in various institutional settings. Additionally sets out how the municipal administration has been co-opted by traditional political actors who, through the maintenance of client relations, have retained the control of local political power. To this add the presence of illegal armed groups in the area, which have conditioned the different Governments.